How the "EU Innovation Champions" successfully absorbed and reacted to the shock caused by the COVID-19 pandemic - Alfredo De Massis; Alberto Di Minin; Cristina Marullo; Paola Rovelli; Rik Tensen; Antonio Carbone; Antonio Crupi (European Commission, Joint Research Centre (JRC), 2020)
The COVID-19 pandemic presented great challenges, but also opportunities, to SMEs across Europe. We examine how the "European Innovation Champions" successfully absorbed and reacted to the shock caused by the COVID-19 pandemic. Five different paradoxical behaviors (i.e., planning, liquidity, time and velocity, partnership, resources and technology) characterized the European Innovation Champions during the peak of the COVID-19 pandemic. We distill 10 management principles representing key actions and decisions that allowed the European Innovation Champions to manage each paradox. This report provides policymakers and business leaders both within and outside the European Union with insights to enhance the capability of SMEs to succeed through a crisis.
Keywords: 330; innovation; SMEs; COVID-19